The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.socscimed.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of community health worker programmes in the late apartheid era in South Africa: An historical analysis

Abstract: There is re-emerging interest in community health workers (CHWs) as part of wider policies regarding task-shifting within human resources for health. This paper examines the history of CHW programmes established in South Africa in the later apartheid years (1970s–1994) – a time of innovative initiatives. After 1994, the new democratic government embraced primary healthcare (PHC), however CHW initiatives were not included in their health plan and most of these programmes subsequently collapsed. Since then a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 13 publications
1
101
0
1
Order By: Relevance
“…The manner of selection and training, payment and incentives, career advancement opportunities, and supervision also vary broadly (25,44,88). Recent estimates have suggested that as many as 85,000-200,000 CHWs function in various roles in the United States (25,36,132). In other countries around the world, a conservative estimate is that there are more than 5 million CHWs, including 2.3 million in India alone (Figure 1).…”
Section: Who Are Community Health Workers?mentioning
confidence: 99%
“…The manner of selection and training, payment and incentives, career advancement opportunities, and supervision also vary broadly (25,44,88). Recent estimates have suggested that as many as 85,000-200,000 CHWs function in various roles in the United States (25,36,132). In other countries around the world, a conservative estimate is that there are more than 5 million CHWs, including 2.3 million in India alone (Figure 1).…”
Section: Who Are Community Health Workers?mentioning
confidence: 99%
“…Health system reform immediately after apartheid was mostly technicist and disease oriented and CHWs were left out of public health policy and strategy (Coovadia, Jewkes, Barron, Sanders, & McIntyre, 2009;van Ginneken et al, 2010).…”
Section: Economic Motivations For Careworkmentioning
confidence: 99%
“…The first is the recognition that HIV-related funding may have diverted vital resources away from other necessary health-related interventions, and a consequent drying up of 'HIV money' among many South African NGOs relatively accustomed to plentiful funding. The second is a shift towards channelling donor funding through the state (van Ginneken et al, 2010) and growing international trust in South Africa's political leadership to effectively use global public health funding.…”
Section: Economic Motivations In Relationshipmentioning
confidence: 99%
“…embraces a variety of selected community based health aids, who are given basic short-term training to work in their communities (Lewin et al, 2010). It is widely acknowledged that CHWs must respond to local societal and cultural norms and customs to safeguard community acceptance and ownership of them (Lehmann & Sanders, 2007a).…”
mentioning
confidence: 99%
“…While it was initially expected that CHW programmes would appeal to mass voluntarism, in practice many programmes have financially rewarded CHWs, even hiring them as salaried assistants (Bloom & Standing, 2001;Hongoro & McPake, 2004). However, such financial incentives lead to high attrition (Kironde & Klaasen, 2002;van Ginneken, Lewin, & Berridge, 2010), especially since they often consist of small token allowances (Eng & Parker, 2002;Hadi, 2003).…”
mentioning
confidence: 99%